Development of efficiency analysis for I-beam steel section with web opening via numerical method - De' nan, Fatimah; Hashim, Nor Salwani; Singh, Amarpreet Kaur Mahinder (2022)
Purpose – Due to the enormous increase in economic development, structural steel material gives an advantage for the construction of stadiums, factories, bridges and cities building design. The purpose of this study is to investigate the behaviour of bending, buckling and torsion for I-beam steel section with and without web opening using non-linear finite element analysis. Design/methodology/approach – The control model was simulated via LUSAS software with the four main parameters which included opening size, layout, shape and orientation. The analysis used a constant beam span which is 3.5m while the edge distance from the centre of the opening to the edge of the beam is kept constant at 250mm at each end. Findings – The analysis results show that the optimum opening size obtained is 0.65 D while optimum layout of opening is Layout 1 with nine web openings. Under bending behaviour, steel section with octagon shapes of web opening shows the highest yield load, yield moment and thus highest structural efficiency as compared to other shapes of openings. Besides, square shape of web opening has the highest structural efficiency under buckling behaviour. The lower buckling load and buckling moment contribute to the higher structural efficiency. Originality/value – Further, the square web opening with counter clockwise has the highest structural efficiency under torsion behaviour.